Institutional assessment of the international criminal court: the pre-trial chamber and the office of the prosecutor: a judicial or a quasi-judicial relationship? - Baldwin-Meenda, Shirley (Department of Public Law, 2026)
This thesis assesses the relationship between the Pre-Trial Chamber and the Office of the Prosecution of the International Criminal Court. It examines the relationship between the two respective organs of the court as laid down in the court's statute and Rules of procedure and Evidence and in practice. The purpose of the assessment is to establish whether the judicial relationship between the two organs laid down in the provision is honoured in practice or is the pre-trial chamber over stepping its boundaries and hence shifting the equilibrium of legal traditions reached in Rome. The research is based primarily on the provisions governing the court and the jurisprudence of the Pre-Trial division of the court.